PHILOSOPHY OF EDUCATION ACCORDING TO SHAYKH ABDULLAH FAHIM - Khairul Nizam bin Zainal Badri (Universitas PGRI Madiun, 2021)
Educational philosophy is a combination of thought and implementation that refers to the theoretical framework of educational purposes and methods. The five main components that form the philosophy of education are ta'lim, tarbiyyah, ta'dib, tadris and tazkiyyah. This study seeks to examine the educational philosophy of Shaykh Abdullah Fahim based on the education system he has introduced. Further to be examined is the effectiveness of the philosophy of education based on his application in the administration of education. And last but not least is the significance of Shaykh Abdullah Fahim's educational philosophy to the development and progress of society. For the purpose of the study, qualitative methods were used. The library approach was chosen to collect information related to the views of Shaykh Abdullah Fahim in the field of education and analyze the information to achieve the objectives of the study. The results of the study found that the philosophy of education of Shaykh Abdullah Fahim takes into account current developments in the country. The philosophy of education that he put forward emphasizes the understanding of religion and the spirit of national consciousness in the souls of his students.